Sequence analysis of control region (D-Loop) of mtDNA from five Vietnamese individuals - Huệ, Huỳnh Thị Thu; Yến, Hoàng Thị Thu; Tôn, Nguyễn Đăng; Hiền, Lê Thị Thu; Cường, Nguyễn Đinh; Chi, Phan Văn; Hải, Nông Văn (Vietnam Journal of Biotechnology, 2008)
Journal of Biotechnology 3(1): 15-22, 2005